High thermoelectric figure of merit by resonant dopant in half-Heusler alloys - Long Chen; Yamei Liu; Jian He; Terry M. Tritt; S. Joseph Poon (AIP Advances, 2017)
Half-Heusler alloys have been one of the benchmark high temperature thermoelectric materials owing to their thermal stability and promising figure of merit ZT. Simonson et al. early showed that small amounts of vanadium doped in Hf0.75Zr0.25NiSn enhanced the Seebeck coefficient and correlated the change with the increased density of states near the Fermi level. We herein report a systematic study on the role of vanadium (V), niobium (Nb), and tantalum (Ta) as prospective resonant dopants in enhancing the ZT of n-type half-Heusler alloys based on Hf0.6Zr0.4NiSn0.995Sb0.005. The V doping was found to increase the Seebeck coefficient in the temperature range 300-1000 K, consistent with a resonant doping scheme. In contrast, Nb and Ta act as normal n-type dopants, as evident by the systematic decrease in electrical resistivity and Seebeck coefficient. The combination of enhanced Seebeck coefficient due to the presence of V resonant states and the reduced thermal conductivity has led to a state-of-the-art ZT of 1.3 near 850 K in n-type (Hf0.6Zr0.4)0.99V0.01NiSn0.995Sb0.005 alloys.